1997
DOI: 10.1029/97ja02034
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal variation of quasi‐biennial oscillation modulation of the semidiurnal tide in the lower thermosphere

Abstract: Abstract. Perturbations in the geomagnetic field at the Earth's surface can result from variations in the neutral wind field in the lower therrnosphere through dynamo action in the interfused ionospheric E region. Thus spectral analysis of the $q variations in ground-based geomagnetic data extending continuously over many years, and from several sites worldwide, has been carried out to investigate the variation with latitude of quasi-biennial oscillation (QBO) effects in the semidiurnal tide in the lower therr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Angelats i Coll and Forbes, 2002). Such a QBO dependence of the semidiurnal tides had previously been observed in the dynamo region (100-140 km) derived from the Sq variation in the H component of the geomagnetic field at high southern latitudes (Jarvis, 1996(Jarvis, , 1997. More recently Xu et al (2009) have presented evidence for a similar biennial periodicity in the summer time semidiurnal tide in the MLT above Rothera.…”
Section: Introductionmentioning
confidence: 78%
“…Angelats i Coll and Forbes, 2002). Such a QBO dependence of the semidiurnal tides had previously been observed in the dynamo region (100-140 km) derived from the Sq variation in the H component of the geomagnetic field at high southern latitudes (Jarvis, 1996(Jarvis, , 1997. More recently Xu et al (2009) have presented evidence for a similar biennial periodicity in the summer time semidiurnal tide in the MLT above Rothera.…”
Section: Introductionmentioning
confidence: 78%
“…Similarly, the quasi‐biennial oscillation (QBO) in the stratosphere and mesosphere has some influence on tidal propagation [ Hagan et al , ; Xu et al , ]. Indeed, Olsen [] and Jarvis [, ] reported small but significant QBO signatures in the S variation. The effect of ENSO and QBO on the lunar tide, however, has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a signature of the quasi biennial oscillation exists in the amplitude of the semidiurnal geomagnetic variation at the equator (Olsen, 1994) and at a range of other latitudes (Jarvis, 1996(Jarvis, , 1997. Kohsiek et al (1995) reported 10-and 16-day oscillations, indicative of planetary wave action associated with natural resonances or Rossby normal modes of the atmosphere (Salby, 1984), in geomagnetic data from two mid-latitude stations in the northern hemisphere.…”
Section: Background To Techniquementioning
confidence: 97%